2021
DOI: 10.1109/access.2021.3054905
|View full text |Cite
|
Sign up to set email alerts
|

Parallelizing Shared File I/O Operations of NVM File System for Manycore Servers

Abstract: NOVA, a state-of-the-art non-volatile memory (NVM) le system, has limited performance due to its coarse-grained per-le lock when multiple threads perform I/Os to a shared le in a manycore environment. For instance, a writer lock blocks other threads attempting to access the same le, although they access di erent regions of a le. When multiple threads reading the same le share a cache line containing a reader counter, performance can be signi cantly degraded due to cache consistency protocol as we increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We note that the applicability of range locks extends beyond the virtual memory management subsystem. As Kim et al demonstrated recently [24], range locks can be used to optimize shared file I/O operations in a file system; we believe that the range locks we present in this paper can be used as a drop-in replacement for the implementation used in [24]. More generally, drawing from the original motivation behind the concept of range locks, the ideas presented in this paper appear to be a natural fit for parallel file systems; we plan to experiment with such systems in the future work.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…We note that the applicability of range locks extends beyond the virtual memory management subsystem. As Kim et al demonstrated recently [24], range locks can be used to optimize shared file I/O operations in a file system; we believe that the range locks we present in this paper can be used as a drop-in replacement for the implementation used in [24]. More generally, drawing from the original motivation behind the concept of range locks, the ideas presented in this paper appear to be a natural fit for parallel file systems; we plan to experiment with such systems in the future work.…”
Section: Introductionmentioning
confidence: 77%
“…In a recent and highly relevant work [24], Kim et al consider using range locks in the context of parallel file systems, and make a similar observation regarding the lack of scalability of the existing kernel range locks. They followed an alternative design for range locks, which was previously proposed by Quinson et al [33], in which the entire range is divided into (a preset number of) segments, each associated with a reader-writer lock.…”
Section: Related Workmentioning
confidence: 94%
See 3 more Smart Citations